Feedback Regulation between Aquatic Microorganisms and the Bloom-Forming Cyanobacterium Microcystis aeruginosa - Zhang, Meng (Appl Environ Microbiol, 2019)
The frequency and intensity of cyanobacterial blooms are increasing worldwide. Interactions between toxic cyanobacteria and aquatic microorganisms need to be critically evaluated to understand microbial drivers and modulators of the blooms. In this study, we applied 16S/18S rRNA gene sequencing and metabolomics analyses to measure the microbial community composition and metabolic responses of the cyanobacterium Microcystis aeruginosa in a coculture system receiving dissolved inorganic nitrogen and phosphorus (DIP) close to representative concentrations in Lake Taihu, China. M. aeruginosa secreted alkaline phosphatase using a DIP source produced by moribund and decaying microorganisms when the P source was insufficient. During this process, M. aeruginosa accumulated several intermediates in energy metabolism pathways to provide energy for sustained high growth rates and increased intracellular sugars to enhance its competitive capacity and ability to defend itself against microbial attack. It also produced a variety of toxic substances, including microcystins, to inhibit metabolite formation via energy metabolism pathways of aquatic microorganisms, leading to a negative effect on bacterial and eukaryotic microbial richness and diversity. Overall, compared with the monoculture system, the growth of M. aeruginosa was accelerated in coculture, while the growth of some cooccurring microorganisms was inhibited, with the diversity and richness of eukaryotic microorganisms being more negatively impacted than those of prokaryotic microorganisms. These findings provide valuable information for clarifying how M. aeruginosa can potentially modulate its associations with other microorganisms, with ramifications for its dominance in aquatic ecosystems. IMPORTANCE We measured the microbial community composition and metabolic responses of Microcystis aeruginosa in a microcosm coculture system receiving dissolved inorganic nitrogen and phosphorus (DIP) close to the average concentrations in Lake Taihu. In the coculture system, DIP is depleted and the growth and production of aquatic microorganisms can be stressed by a lack of DIP availability. M. aeruginosa could accelerate its growth via interactions with specific cooccurring microorganisms and the accumulation of several intermediates in energy metabolism-related pathways. Furthermore, M. aeruginosa can decrease the carbohydrate metabolism of cooccurring aquatic microorganisms and thus disrupt microbial activities in the coculture. This also had a negative effect on bacterial and eukaryotic microbial richness and diversity. Microcystin was capable of decreasing the biomass of total phytoplankton in aquatic microcosms. Overall, compared to the monoculture, the growth of total aquatic microorganisms is inhibited, with the diversity and richness of eukaryotic microorganisms being more negatively impacted than those of prokaryotic microorganisms. The only exception is M. aeruginosa in the coculture system, whose growth was accelerated.